Peningkatan Literasi Digital dan Analisis Data UMKM Melalui Pelatihan SPSS bagi Wirausaha Muda - Nayla Desviona; Marwah Masruroh; Lizabeth Sari Dewi; Asramid Yasin (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the national economy that continues to show significant growth, especially among the younger generation. The high entrepreneurial spirit encourages many generations to start businesses with creative ideas that are relevant to the times. However, behind the growth of MSMEs, there are still many challenges that must be faced by business actors. One of the main challenges is the lack of ability to manage and analyze data systematically. This community service activity aims to improve the digital literacy and data analysis skills of MSME players, especially the younger generation who are starting a business by utilizing SPSS as an analysis tool. Through practice-based training conducted online through Zoom Meeting involving 40 participants from the younger generation who are starting a business on February 15, 2025. The results of this service showed that participants not only gained a theoretical understanding of the importance of data analysis in making business decisions, but also basic technical skills in operating SPSS. This shows that digital practice-based training has a significant impact in improving their readiness to apply SPSS in managing their business and the competitiveness of MSMEs. Thus, this activity is not only an educational event, but also triggers awareness of the importance of a data-driven approach in dealing with market dynamics.